EFFICIENCY OF WASTEWATER TREATMENT BY A MIXTURE OF SLUDGE AND MICROALGAE - Khaldi, H.; Maatoug, M.; Heilmeier, H.; Dellal, A. (University of Eloued جامعة الوادي, 2017)
A combined system using the microalgae from South Africa and the sewage sludge from Algeria has been tested, in order to study the efficiency of wastewater treatment by mixtures of microalgae / activated sludge, five bioreactors were installed with different inoculation rates (microalgae / activated sludge) B1: 100% algae, B2: 90.90%: 9.1%, B3: 83.33%: 16.67%, B4: 50%: 50% and B5: 16.67: 83.33. The best removal percentages were measured as: 76.36% for PO4-P, 94.90% for NO3-N, 90.42% for NH4-N and 65.73% for COD, in the combined system. Except in the case of COD, there were highly significant effects of different inoculations rates on yield. The best results are those of the bioreactor B5. These results suggest that the nutrients in the wastewater can be effectively eliminated by co-cultivation of micro-algae with bacteria (activated sludge).
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Wastewater; phosphates; nitrates; ammonium; COD; microalgae / activated sludge; bioreactor.